National and regional death burden attributable to ambient temperatures: epidemiological evidence from 89 Chinese communities. (October 2016) - Yang, Jun; Zhou, Maigeng; Yin, Peng; Li, Mengmeng; Liu, Xiaobo; Wu, Haixia; Liu, Qiyong
Abstract: Background: Ambient temperature is an important risk factor for human health. However, little evidence is available on the attributable burden, such as absolute or relative excess of mortality, due to temperature. We investigated the burden ofdeath attributable toambient temperature in China. Methods: We used the national database comprising daily death data for 89 Chinese communities for 2007–2013, covering 106·1 million permanent residents, according to China's 2010 population census. A distributed lag non-linear model was used to estimate the community-specific mortality effects of daily mean temperature. Pooled estimates of national and regional effects (southern, northern, western and eastern; rural and urban), were then calculated through multivariate meta-analysis. Attributable deaths were calculated for cold and heat, defined as ambient temperatures below and above the minimum-mortality temperature. This study was approved by the ethics committee of the Chinese Center for Disease Control and Prevention (201214). Findings: Our analysis included 1 727 143 non-accidental deaths during the study period, with a total of 228 213 (95% empirical CI 192 835–244 597) deaths attributed to non-optimum ambient temperatures. The national attributable fraction was 13·21% (95% empirical CI 11·34–14·16), most of which was linked to low temperatures (11·96%, 10·04–12·94). There was significant between-region heterogeneity in the attributable fractions for non-optimal temperature (I 2 =56·1%, p<0·0001, ranging from 12·18% (8·49–14·33) in northern regions to 18·16% (8·73–22·92) in western regions. Death burdens attributed to ambient temperatures were similar between urban (13·37%, 10·68–15·09) and rural regions (13·46%, 10·46–15·08). Interpretation: Ambient temperature was responsible for 13·21% of deaths in China, and the burden attributable to this factor varied significantly across different regions. Most of this burden was caused by low temperature. This study has implications for policymakers developing protective strategies to mitigate the health effects of adverse ambient temperatures. Funding: National Basic Research Program of China (973 Program) (Grant No 2012CB955504 ). No funding bodies had any role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.